Kinerja dan perbandingan pengembalian pasar di Asia - Duwith, Elisabeth Marjem; Aloo, Susi (Riset Akuntansi dan Manajemen Pragmatis, 2023)
At the beginning of 2023, economic conditions due to global issues will still significantly influence world markets. This study aims to compare the market return performance in Asia, namely Indonesia, South Korea, Japan, China, India, Taiwan, Vietnam, Malaysia, the Philippines, Thailand, Singapore, and Hong Kong. Evidence suggests that South Korea and Taiwan tend to have higher market returns than other Asian countries. Therefore, the risk-return tradeoff conditions in South Korea and Taiwan tend to be more optimal. Other findings also show that market returns for countries that are members of ASEAN-5 and India tend to be below the median of other Asian countries. Throughout the observation period, the Hong Kong market tends to be more risky while the Malaysian market tends to be less risky. Specifically, the findings show that markets in Indonesia, China, India, Vietnam, the Philippines, Singapore, and Hong Kong are not significantly different from each other or from other Asian markets.